Kinerja Keuangan Bank Syariah Mandiri: Sebelum dan Sesudah Penerapan Good Corporate Governance - Sabirin Sabirin (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
This research aims to determine the Financial Performance Assessment Before and After Implementation of Good Corporate Governance (GCG) seen from the ratio (1) Liquidity, (2) Profitability, and (3) Capital. The research method is quantitative research with a comparative approach. The ratio used to measure the financial performance of Bank Syariah Mandiri Tbk consists of the ratio of FDR, ROA, ROE, and CAR. The data analysis technique used is the data Normality and the Mann-Whitney test. The results of this study based on the normality test show that the data are normally distributed. The Mann-Whitney test results show that (1) after implementing GCG, liquidity ratio has satisfactory performance assessment compared to before the implementation of GCG. (2) After implementing GCG, profitability ratio has satisfactory performance assessment compared to before the implementation of GCG. (3) After implementing GCG, the capital ratio has a satisfactory performance assessment compared to before the implementation of GCG